UPAYA PENGEMBANGAN TUMBUHAN HIDROPONIK BERBASIS MEDIA IKAN LELE DI DESA KAMPUNG KUSAMBA - Putu Irma Yunita; I Dewa Putu Dipta Maharta; I Putu Dharmawan Pradhana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Kampung Kusamba Village is one of the villages located in Klungkung Regency, Bali.The village has minimal land to grow vegetables. This is because this village has an area of 2.01 km2 located on the coast.This condition eventually caused problems for residents in growing vegetables.So the solution that the author can offer is to develop hydroponic land for residents by combining Hydroponics with aquaponics based on catfish media intended for the residents of Kusamba Village.From the manufacture of catfish-based hydroponics, it can take advantage of minimal vacant land for planting hydroponic plants